2002
DOI: 10.1577/1548-8667(2002)014<0001:aiiama>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Aphanomyces invadansin Atlantic Menhaden along the East Coast of the United States

Abstract: The cause of deeply penetrating ulcers of Atlantic menhaden Brevoortia tyrannus has been the subject of significant research efforts in recent years. These lesions and the associated syndrome termed ulcerative mycosis have been observed along the East Coast of the United States since at least the early 1980s. Although Aphanomyces spp. were isolated from these lesions in the mid to late 1980s, similar lesions could not be reproduced by experimental infections of Atlantic menhaden with these isolates. The identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 25 publications
4
58
0
Order By: Relevance
“…Histological examination of these lesions has shown that they are chronic, and the majority can be characterized as ulcerative mycosis , Kane et al 1998, Blazer et al 1999. Recently, the fungal agent associated with ulcerative mycosis in Atlantic menhaden has been identified as Aphanomyces invadans (Blazer et al 2002). Lesions identical to those observed in the wild have been reproduced by injection and bath exposure to fungal zoospores (Kiryu et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Histological examination of these lesions has shown that they are chronic, and the majority can be characterized as ulcerative mycosis , Kane et al 1998, Blazer et al 1999. Recently, the fungal agent associated with ulcerative mycosis in Atlantic menhaden has been identified as Aphanomyces invadans (Blazer et al 2002). Lesions identical to those observed in the wild have been reproduced by injection and bath exposure to fungal zoospores (Kiryu et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Pathological surveys of skin ulcers revealed that most contained oomycetes (filamentous protists that physically resemble fungi) (2,24,34). Specialized culture techniques were developed to isolate and identify these oomycetes (3,13,46). A number of species belonging to genera as diverse as Aphanomyces, Saprolegnia, and Achlya were recovered (4,12,40).…”
mentioning
confidence: 99%
“…Saprolegnia spp. has been reported in waters of Japan, Philipines, Australia and throughout the South Asia (Blazer et al, 2002). Simultaneous improvisation in expertise and facilities in disease diagnosis have led to the identification of several previously unknown pathogens and diseased conditions.…”
Section: Introduction Presence Of Saprolegnia Spp (Oomycetes) In Thementioning
confidence: 99%